(untitled) (Medico Legal Update, 2022)
Background: Behavioral disturbance is a common problem for teenagers all over the world. The prevalence of behavioral disturbance depends on age, family environment, school environment, and friend relationships.The aim of the study to determine the prevalence of behavioral disturbance patterns among male students from age 13-19 yrs. In public secondary schools in Baghdad, Iraq.Methods: Cross-sectional study done in public secondary schools in Baghdad for educational year 2020 - 2021.The sample was collected by multistage cluster sampling from 6 schools .Data collection was done through self-administered questionnaire from 7th February 2021 to 16th march 2021. The questionnaire is comprised of two parts; part 1 was made of demographic characteristics and behavioral disturbance manifestations. Part 2 comprised of socioeconomic characteristics. Results: 600 students were participated in this study the mean age 15.51.3 . Substance use disorder (15.8%) and bullying (13.5%) were the common forms of behavioral disturbance. Conclusion: high rates of all behavioral disturbance were noticed among secondary school students including bullying, substance use disorder, Rebellion and pornography.